African Descent and Glaucoma Evaluation Study (ADAGES): II. Ancestry Differences in Optic Disc, Retinal Nerve Fiber Layer, and Macular Structure in Healthy Subjects - Girkin, Christopher A. (2010)
OBJECTIVE: To define differences in optic disc, retinal nerve fiber layer, and macular structure between healthy participants of African (AD) and European descent (ED) using quantitative imaging techniques in the African Descent and Glaucoma Evaluation Study (ADAGES). METHODS: Reliable images were obtained using stereoscopic photography, confocal scanning laser ophthalmoscopy (Heidelberg retina tomography [HRT]), and optical coherence tomography (OCT) for 648 healthy subjects in ADAGES. Findings were compared and adjusted for age, optic disc area, and reference plane height where appropriate. RESULTS: The AD participants had significantly greater optic disc area on HRT (2.06 mm(2); P<.001) and OCT (2.47 mm(2); P<.001) and a deeper HRT cup depth than the ED group (P<.001). Retinal nerve fiber layer thickness was greater in the AD group except within the temporal region, where it was significantly thinner. Central macular thickness and volume were less in the AD group. CONCLUSIONS: Most of the variations in optic nerve morphologic characteristics between the AD and ED groups are due to differences in disc area. However, differences remain in HRT cup depth, OCT macular thickness and volume, and OCT retinal nerve fiber layer thickness independent of these variables. These differences should be considered in the determination of disease status.